Investigation of the chemical structure of anti-amyloidogenic constituents extracted from Thamnolia vermicularis. (10th May 2022) - Yu, Xiaobo; Cai, Yisheng; Zhao, Xu; Wu, Chenyu; Liu, Junqing; Niu, Tingting; Shan, Xu; Lu, Yanjie; Ruan, Yanan; He, Jianwei
Abstract: Ethnopharmacological relevance: Thamnolia vermicularis (Sw.) Schaer ( T. vermicularis ) is known to have therapeutic effects on various diseases in Southwest China. Recent research has highlighted that T. vermicularis may suppress Aβ level and Tau hyperphosphorylation to improve the pathological characteristics of Alzheimer's disease, indicating that it might have the potential to treat Alzheimer's disease. Aim of the study : The objective of this study was to evaluate the inhibitory effect of T. vermicularis on the fibril formation of a typical amyloidogenic protein, hen egg white lysozyme (HEWL), and to identify the effective components that could potentially enable an extract of T. vermicularis to be used in the development of novel therapeutic agents. Materials and methods: A water extract was prepared from T. vermicularis (TVWE) and its inhibitory effect on amyloid fibrillation in vitro was investigated using thioflavin T and 8-anilinonapthalene-1-sulfonic acid spectrofluorometric analyses. The anti-amyloidogenic components of TVWE were separated and qualitatively analyzed using thin layer chromatography (TLC), supercritical carbon dioxide extraction (SFE-CO2 ), and liquid chromatography-mass spectrometry. Finally, the effect of the bioactive components on the structure of HEWL in the early stages of fibrillogenesis was determined by molecular docking simulation. Results: TVWE strongly inhibited the ability of HEWL to form an amyloid fibril, yielding an IC50 of 0.018 mg/mL for the inhibition of fibrillogenesis. The chemical constituents in the various TVWE fractions resolved by TLC were qualitatively identified by liquid chromatography-quadrupole/time-of-flight mass spectrometry (LC-Q-TOF-MS). The target components were predicted by reviewing the existing literature on T. vermicularis, in which the components of T. vermicularis, along with three small molecules (molecular weight: 182) were preliminarily identified. Molecular docking simulation showed that these small molecules were bound to the core region of HEWL, affecting its stability. Finally, the active anti-amyloidogenic components were extracted from whole T. vermicularis using SFE-CO2 and then identified. Conclusion: The potential components of TVWE that could prevent HEWL fibrillogenesis were primarily identified using TLC, LC-Q-TOF-MS, and SFE-CO2. The candidate small-molecule compounds were further predicted by combining the LC-Q-TOF-MS results with molecular docking analysis. The effective components of T. vermicularis were extracted using SFE-CO2 . Together, these methods could constitute a practical strategy for the isolation and identification of anti-amyloidogenic components from a traditional Chinese medicine. Graphical abstract: Image 1 Highlights: Protein-misfolding diseases are an increasing concern in our rapidly aging society. Tea made from T. vermicularis can prevent or attenuate these diseases. We extracted three possible compounds that prevent fibrillogenesis. The effective components of T. vermicularis were extracted using SFE-CO2 extraction.